The Application of Artificial Intelligence in China’s Criminal Justice System - Guo, Zhiyuan; Yang, Jiajia (Legal Issues in the Digital Age, 2025)
Influenced by the advanced technologies, in recent years, Chinese criminal justice system has begun integrating artificial intelligence (AI) to assist judicial decision-making. AI has entered into various areas such as criminal investigations, prosecution assistance, and sentencing support. However, Chinese legal system has not comprehensively addressed the regulation of judicial AI technology yet. This paper aims to explore the application of AI in Chinese criminal justice system and propose a systematic regulatory framework for its future development. Part I provides an overview of the specific application scenarios of AI in Chinese criminal justice system. Part II analyzes the general characteristics of judicial AI and the benefits it brings to the justice system. Part III examines the challenges limiting the further development of judicial AI and the potential risks associated with its application. Part IV proposes an inclusive regulatory framework to balance the intension and potential conflicts between judicial fairness and technological advancement. This research seeks to enhance the understanding of AI application in Chinese criminal justice system and to identify and prevent potential judicial risks arising from AI application.